Education Funding and Student Outcomes: A Conceptual Framework for Measurement of the Alignment of State Education Finance and Academic Accountability Policies - Robert C. Knoeppel; Matthew R. Della Sala (Educational Considerations, 2015)
The conceptualization and measurement of education finance equity and adequacy has engaged researchers for more than three decades. At the same time, calls for increased academic accountability and higher student achievement in K-12 public education have reached new levels at both the national and state levels.
Keywords: student outcomes; conceptual framework; accountability policies; National Assessment of Educational Progress; NAEP; finance; Judicial Interpretations; academic; education